Explore the role of CBS in stomach adenocarcinoma based on the sulfur-containing amino acid metabolism network - Ping Zhang; Yingchao Liu; Yajuan Lu; Aoli Deng; Jinghao Cao; Hangqi Huang; Cuiyun Wu; Jing Du; Yanchun Li; Jun Xia (Scientific Reports)
Abstract The sulfur-containing amino acids (SAAs) play a key role in the occurrence and development of tumors. However, the clinical prognostic value of SAAs metabolism (SAAM) regulators in stomach adenocarcinoma (STAD) remains unclear. We systematically evaluated the clinical and immune characteristics of SAAM-related genes in STAD. Furthermore, a SAAM score model was constructed, and patients in the low-SAAM score group had a better prognosis. As the core gene in the model, the low expression of cystathionine beta-synthase (CBS) indicated a better prognosis for patients. Interfering with CBS expression in MKN-45 cells inhibited cell proliferation, reduced the production of glutathione (GSH), and promoted cellular oxidative stress. Importantly, the downregulation of CBS heightened sensitivity to ferroptosis inducers in STAD cells, highlighting the involvement of CBS in ferroptosis. In conclusion, the utilization of SAAM for the identification and personalized scoring of patients might potentially play a significant role in evaluating prognosis, immune infiltrates, and guiding treatment for STAD.